Building seismic monitoring and detection technology : proceedings of the 2nd International Conference on Structural Seismic Resistance, Monitoring and Detection (SSRMD 2023), Xiamen, China, 6-8 January 2023 /: proceedings of the 2nd International Conference on Structural Seismic Resistance, Monitoring and Detection (SSRMD 2023), Xiamen, China, 6-8 January 2023. (2023) - Unknown
No abstract available